Mechanisms of Thrombosis in Heparin-Induced Thrombocytopenia and Vaccine-Induced Immune Thrombotic Thrombocytopenia - Selvadurai, Maria V.; Favaloro, Emmanuel J.; Chen, Vivien M. (Seminars in Thrombosis and Hemostasis, 2023)
Heparin-induced thrombocytopenia (HIT) and vaccine-induced immune thrombotic thrombocytopenia (VITT) are rare, iatrogenic immune-mediated conditions with high rates of thrombosis-related morbidity and mortality. HIT is a long-recognized reaction to the administration of the common parenterally administered anticoagulant heparin (or its derivatives), while VITT is a new, distinct syndrome occurring in response to adenovirus-based vaccines against coronavirus disease 2019 and potentially other types of vaccines. A feature of both HIT and VITT is paradoxical thrombosis despite a characteristic low platelet count, mediated by the presence of platelet-activating antibodies to platelet factor 4. Several additional factors have also been suggested to contribute to clot formation in HIT and/or VITT, including monocytes, tissue factor, microparticles, endothelium, the formation of neutrophil extracellular traps, complement, procoagulant platelets, and vaccine components. In this review, we discuss the literature to date regarding mechanisms contributing to thrombosis in both HIT and VITT and explore the pathophysiological similarities and differences between the two conditions.
Keywords: heparin-induced thrombocytopenia; vaccine-induced thrombotic thrombocytopenia; thrombosis; platelet factor 4